2017
DOI: 10.3389/fphys.2017.01089
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Translocating Nicotinamide Nucleotide Transhydrogenase: A Structural Perspective

Abstract: Nicotinamide nucleotide transhydrogenase (TH) is an enzyme complex in animal mitochondria and bacteria that utilizes the electrochemical proton gradient across membranes to drive the production of NADPH. The enzyme plays an important role in maintaining the redox balance of cells with implications in aging and a number of human diseases. TH exists as a homodimer with each protomer containing a proton-translocating transmembrane domain and two soluble nucleotide binding domains that mediate hydride transfer bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Conversion of NAD + to NADP + is catalyzed by NAD + kinase consuming ATP molecules for needed free energy [ 30 ]. Nicotinamide nucleotide transhydrogenase (NNT) catalyzes a reversible reaction, NADH + NADP + ⇌ NAD + + NADPH [ 31 ]. NAD(H) and NADP(H) play as cofactors or coenzymes in a myriad of oxidation-reduction reactions in biological systems [ 32 ].…”
Section: Metabolism Of Nicotinamidementioning
confidence: 99%
“…Conversion of NAD + to NADP + is catalyzed by NAD + kinase consuming ATP molecules for needed free energy [ 30 ]. Nicotinamide nucleotide transhydrogenase (NNT) catalyzes a reversible reaction, NADH + NADP + ⇌ NAD + + NADPH [ 31 ]. NAD(H) and NADP(H) play as cofactors or coenzymes in a myriad of oxidation-reduction reactions in biological systems [ 32 ].…”
Section: Metabolism Of Nicotinamidementioning
confidence: 99%
“…It has also been found that mitochondria contain a matrix-associated glucose-6-phosphate dehydrogenase (G6PDH) isozyme, which has been speculated to play a role in the production of mitochondrial ribose sugars for nucleotide biosynthesis [ 33 ]. Unlike the other NADPH producers, which simply couple the oxidation of carbon to the reduction of NADP + , NNT actually assembles in the mitochondrial inner membrane and couples proton return to the matrix to the transfer of a hydride from NADH to NADP + [ 34 ].…”
Section: Mitochondrial H 2 O 2 mentioning
confidence: 99%
“…A TMHMM search [19] suggested that EgNNT1 contained at least 12 transmembrane domains. According to the localization of NNTs in other organisms [20], EgNNT1 was predicted to localize in the mitochondrial inner membrane.…”
Section: Effect Of Egnnt1 Silencing In the Aerobic And Anaerobic Culturesmentioning
confidence: 99%